Sistem Pendukung Keputusan Penerimaan Bantuan Beras Miskin Menggunakan Metode AHP (Analytical Hierarchy Process) Pada Kecamatan Banawa - Kusumawati, Dewi; Mohammad, Mohammad (ScientiCO : Computer Science and Informatics Journal, 2018)
The rice program for poor families or commonly known as Raskin is one of the government's efforts to reduce the burden of expenditure on poor families. The Raskin program is to reduce poverty and maintain the food of economically disadvantaged people so that all parties are expected to participate in the success of this program so that it can be implemented properly and is beneficial to the community. In general, the problems that occur in the assistance of Poor Rice assistance are still not optimal, because at the time of selection of poor rice recipients there is no system that supports so that during the selection process still using estimates only and there is no calculation at the time of selection of poor rice recipients. So that few or many people sometimes protest because people are supposed to get help but they don't get the assistance, and vice versa. The purpose of this study is to help the committee to receive poor rice assistance in selecting people who are entitled to receive assistance, especially in the district of Banawa. The research method used is the software development method using the prototype method and decision-making method using the AHP (Analytical Hierarchy Process) method. Based on the results of testing conducted with the black box technique, the results show that the decision support system for receiving poor rice assistance can help the sub-district, especially the committee in selecting poor rice aid recipients, by comparing the criteria for each alternative and showing the value the highest of alternatives means that the alternative is the main choice for receiving poor rice assistance.